2001
DOI: 10.1046/j.1365-2591.2001.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Root canal systems of the mandibular and maxillary first permanent molar teeth of South Asian Pakistanis

Abstract: It is concluded that four root canals in mandibular and maxillary first permanent molar teeth of South Asian Pakistanis is a common occurrence. The distribution of the different configurations of root canal systems in this population differed from that in Caucasian groups, suggesting that variations in root canal systems may be attributed to racial divergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
74
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 14 publications
13
74
2
5
Order By: Relevance
“…Similar to our results, the root canal configuration type of the palatal root has been reported in the literature and with even lower variations from the 1-1-1/1 configuration (31,32) in the distobuccal root. In contrast, Wasti et al (30) reported that 33.3% of the palatal roots of the maxillary first molars had a configuration type 1-2. These discrepancies could also be explained through the different type of ethnical samples origin and sample number.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar to our results, the root canal configuration type of the palatal root has been reported in the literature and with even lower variations from the 1-1-1/1 configuration (31,32) in the distobuccal root. In contrast, Wasti et al (30) reported that 33.3% of the palatal roots of the maxillary first molars had a configuration type 1-2. These discrepancies could also be explained through the different type of ethnical samples origin and sample number.…”
Section: Discussionmentioning
confidence: 91%
“…These results are similar to those obtained by Sert and Bayirli (15), who observed 14 additional root canal configurations. However, Thomas et al (29) and Wasti et al (30) report a higher configuration variety. Similar to our results, the root canal configuration type of the palatal root has been reported in the literature and with even lower variations from the 1-1-1/1 configuration (31,32) in the distobuccal root.…”
Section: Discussionmentioning
confidence: 96%
“…In Barbizam (24) study, two palatal and two mesiobuccal rooted maxillary first molars were reported, while we did not find any additional root in this study. 100% of cases indicated by Pattanshetti (25), Wasti (26) and Alavi (12), had one canal of distobuccal and palatal roots in maxillary first molars. whereas Ng (11) found 96% of distobuccal and 100% of palatal roots with one canal.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, Neelakantan et al (1) reported MB 2 in 44.1%; they used another type of CBCT system (3D Accuitomo, Japan). Rathi et al (38) evaluated the frequency of MB 2 by CT and reported its percentage as 57%, while Wasti et al (26) used tooth clearing technique and found the second mesiobuccal frequency in maxillary first molar as 52%. The obtained results of these two studies were lower than this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pomeranz and Fishelberg (3) revealed a large discrepancy between clinical and laboratory results with regard to the incidence of MB2s. Although in vitro studies have also demonstrated that the incidence of MB2s is high, there is no consensus on the number of MB2s that are amenable to endodontic treatment (12,16) . To categorize the root canal system in each root, Weine described four different configurations: type I (a single canal from the pulp chamber to the apex), type II (2 separate canals that leave the chamber but merge short of the apex to form a single canal), type III (2 separate canals that leave the chamber and exit the root in separate foramina), and type IV (1 canal that leaves the chamber but divides short of the apex into 2 separate and distinct canals with separate foramina).…”
Section: Introductionmentioning
confidence: 99%